Serological profile of chronic hepatitis B carriers – A tertiary care experience - Ramamurthy, Swaathy; Rathinam Suresh; Purushothaman Ganesan (Asian Journal of Medical Sciences, 2023)
Background: Hepatitis B virus (HBV) infection in India has prevalence of around 40 million chronic HBV (CHB) carriers; 1 to 2 lakhs reported deaths annually due to its complications, such as cirrhosis and hepatocellular carcinoma. Most are asymptomatic, serving as the source of this highly transmissible infection. These patients must be evaluated and monitored regularly, for prediction of their prognosis to reduce their morbidity and mortality. Aims and Objectives: In this study, asymptomatic CHB carriers are evaluated, to assess the risk factors, and to determine replication markers of HBV and coinfection with hepatitis D virus. Materials and Methods: In this cross-sectional study, 123 asymptomatic CHB carriers were subjected to hepatitis B serological assays such as hepatitis B surface antigen, hepatitis B “e” antigen, anti-hepatitis B “e” antibody, and anti-HDV antibody by enzyme-linked immunosorbent assay. Results: Majority (70%) belonged to the age group of 21–50 years. Replicative carriers (HBeAg+) belonging to the age group below 40 years constituted 75% (P=0.04). The most common risk factor in the study group was frequent therapeutic injections (36.6%) followed by family contacts (33.3%). Significant part of family contacts was replicative carrier (P=0.025). Serological profile showed that 83.3% were HBe-seroconverted, with only16.2% showing HBeAg positivity. No patient showed co/super-infection with HDV. Conclusion: Preponderance of hepatitis B carrier status in young adult males and four fold increased incidence in family contacts than general population necessitates stringent screening of young adults and family contacts. Furthermore, this study mandates regular evaluation of chronic hepatitis B carriers by serological assays for better therapeutic management.